Soil quality, elemental stoichiometry and crop yield under partial substitution of chemical fertilizers with organic inputs in Vertisols: a six-site field study - Jiang, Fahui; Han, Shang; Cheng, Wenlong; Song, Li; Tang, Shan; Wang, Hui; Bu, Rongyan; Li, Min; Zhu, Rui; Islam, Mahbub Ul; Wu, Ji (Frontiers in Plant Science, 2026)
Partial substitution of chemical fertilizers with organic amendments represents a promising approach to sustainable soil management, yet its integrated effects on soil quality and elemental stoichiometry in Vertisols remain insufficiently understood. This study aimed to investigate the impacts of partial organic fertilizer substitution on soil quality, ecological stoichiometry, crop yield, and yield stability through a three-year, six-site field experiment in the North China Plain. Treatments included an unfertilized control, full chemical fertilization (NPK), and NPK partially substituted by pig manure at 15% and 30% of nitrogen input (15%M and 30%M). Results revealed that partial substitution significantly reduced soil bulk density (1.3–17.1%) and increased soil organic carbon (0.77–22.5%) compared with NPK and control plots. While total nitrogen (N), phosphorus (P), and potassium (K) contents were comparable to NPK, nutrient availability improved markedly (2.1–23.7%). Organic inputs also modified soil elemental stoichiometry by increasing C:N, C:P, and N:P ratios, indicating a shift toward more balanced nutrient states. These improvements translated into substantial increases in the Soil Quality Index (31.5–335.6%), which in turn supported significant yield gains in wheat and maize (1.3–251.3%), with the 30%M treatment consistently achieving the greatest benefits. Random forest analysis and structural equation modeling demonstrated that yield responses were predominantly mediated through improvements in soil quality, driven by enhanced nutrient availability and optimized stoichiometry. Overall, our findings suggest that partial substitution of chemical fertilizers with organic inputs-particularly at a 30% replacement rate-offers as an effective strategy to improve soil quality, mitigate nutrient imbalances, and promoting sustainable intensification of wheat–maize systems in Vertisol regions.